2017
DOI: 10.1016/j.alit.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sublingual immunotherapy in a murine asthma model sensitized by intranasal administration of house dust mite extracts

Abstract: These data suggest that earlier induction of SLIT in HDM-sensitized mice provides superior suppression of AHR and goblet cell metaplasia. The modulation of allergen specific IgG2a and local IgA might play a role in the amelioration of AHR and airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…Experimental mouse models of HDM‐SLIT treatment have rendered variable results regarding the efficiency of suppressing the different parameters of allergic airway disease, but generally show limited induction of neutralizing antibody responses, in line with our own results. For instance, in one study using Dermatophagoides farinae (Der f) extracts, SLIT treatment had a more pronounced effect on AHR than on Th2‐driven, eosinophilic airway inflammation . In contrast, a study using both Dermatophagoides pteronyssinus (Der p) and Der f extracts showed a stronger effect on suppression of eosinophilic airway inflammation, while AHR was only suppressed at higher doses of extracts used for SLIT treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental mouse models of HDM‐SLIT treatment have rendered variable results regarding the efficiency of suppressing the different parameters of allergic airway disease, but generally show limited induction of neutralizing antibody responses, in line with our own results. For instance, in one study using Dermatophagoides farinae (Der f) extracts, SLIT treatment had a more pronounced effect on AHR than on Th2‐driven, eosinophilic airway inflammation . In contrast, a study using both Dermatophagoides pteronyssinus (Der p) and Der f extracts showed a stronger effect on suppression of eosinophilic airway inflammation, while AHR was only suppressed at higher doses of extracts used for SLIT treatment .…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of animal models for specific allergen immunotherapy tried optimizing the application mode and route of allergen, by entrapment in tolerogenic PLG particles [46 ▪▪ ], or application concomitantly with CpG [45], probiotics or Vitamin D3 (Table 1) [3739,41,42 ▪ ,43 ▪▪ ,44,45,46 ▪▪ ,49 ▪ ,51]. In particular, epicutaneous application has achieved promising results without adjuvants [43 ▪▪ ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, highly sensitized mice required higher sublingual immunotherapy (SLIT) dose than less sensitized mice to improve airway hyperresponsiveness [37]. Moreover, upon SLIT treatment, a lower proportion of CD4-CD8 γδ cells and a higher frequency of CD8 + CD25 + IFNγ + T cells accompanied by reduced inflammatory responses in the lung were observed [38].…”
Section: Immunomodulation By Allergen-specific Immunotherapymentioning
confidence: 99%
“…Concentrations of Der f 1 and Der f 2 were 4.8 μg/mg extract and 4.0 μg/mg extract, respectively [27]. We measured lipopolysaccharide (LPS) concentrations of Df extract by using an endotoxin-specific chromogenic Limulus test (Endospecy test, Seikagaku Corporation, Tokyo, Japan) in this study and found that the LPS concentration of Df extract at 1,000 ng/mL was 10.7 ± 0.9 pg/mL ( n = 8).…”
Section: Methodsmentioning
confidence: 99%
“…Df was collected and a dried extract prepared as described previously [27]. Concentrations of Der f 1 and Der f 2 were 4.8 μg/mg extract and 4.0 μg/mg extract, respectively [27].…”
Section: Methodsmentioning
confidence: 99%